The role of phytomelatonin receptor 1-mediated signaling in plant growth and stress response - Khan, Dawood; Cai, Nan; Zhu, Weilin; Li, Leilin; Guan, Miao; Pu, Xiaojun; Chen, Qi (Frontiers in Plant Science, 2023)
Phytomelatonin is a pleiotropic signaling molecule that regulates plant growth, development, and stress response. In plant cells, phytomelatonin is synthesized from tryptophan via several consecutive steps that are catalyzed by tryptophan decarboxylase (TDC), tryptamine 5-hydroxylase (T5H), serotonin N-acyltransferase (SNAT), and N-acetylserotonin methyltransferase (ASMT) and/or caffeic acid-3-O-methyltransferase (COMT). Recently, the identification of the phytomelatonin receptor PMTR1 in Arabidopsis has been considered a turning point in plant research, with the function and signal of phytomelatonin emerging as a receptor-based regulatory strategy. In addition, PMTR1 homologs have been identified in several plant species and have been found to regulate seed germination and seedling growth, stomatal closure, leaf senescence, and several stress responses. In this article, we review the recent evidence in our understanding of the PMTR1-mediated regulatory pathways in phytomelatonin signaling under environmental stimuli. Based on structural comparison of the melatonin receptor 1 (MT1) in human and PMTR1 homologs, we propose that the similarity in the three-dimensional structure of the melatonin receptors probably represents a convergent evolution of melatonin recognition in different species.